The legal effect of Licensing contracts in the field of oil investment - سعيد اقبال ناجي (Journal of Legal Sciences, 2019)
Iraq is currently the third largest oil reserves in the world after Saudi Arabia and Iran, which is estimated at (115) billion barrels, in addition to the gas reserves of (119) trillion cubic meters so foreign oil companies have been competing for contracts to participate in production and technical service for years to sign the cost of operations The high productivity, which is based on the payment of the term, which leads to raising the cost of production per barrel, which comes mainly from the employment of foreign workers with high salaries and the provision of local services of high standard and purchase of commodity and consulting services worth hundreds of millions of dollars. And the presence of maneuvering and manipulation by foreign companies to acquire an unfair share of the commercial benefits of their operations, taking advantage of some clauses of the contract that are in their interest, such as the assignment of tenders within their powers to companies of their nationality, which will limit the role of our oil companies and efficient national cadres and turned it into a major contractor and distributed his work The foreign companies are waiting for their profits and will eliminate On the companies of the extractive sector - service companies - as an Iraqi drilling company and the oil projects company, which is basically below the required level because of the technical and administrative negligence that the country is currently undergoing.